2016
DOI: 10.1111/cas.13093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AKT3 expression on MYC‐ and caspase‐8‐dependent apoptosis caused by polo‐like kinase inhibitors in HCT 116 cells

Abstract: Polo‐like kinase (PLK) is a cell‐cycle regulator that is overexpressed in several cancer cell types. Polo‐like kinase is considered a novel target for cancer therapies, and several PLK inhibitors (PLKis), including BI 2536, BI 6727, and GSK461364, have been developed. In this study, we established five BI 2536‐resistant cell lines from human colorectal cancer HCT 116 cells, to explore the resistance mechanism and identify predictable biomarkers of PLKis. We showed that PLKi‐induced caspase‐8 activation was att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Indeed, genes belonging to the ubiquitin-proteasome system can be found in all clusters and PLK1 expression is higher in cluster 2 tumours compared to the others. However, many cell lines have been reported throughout literature to be insensitive to these drugs 51 56 . Moreover, we observed a significant synergic action of Bortezomib and PLK1 inhibitors at several dosages on both cell lines, not found when BI6727 was considered in combination with the other two signature-related drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genes belonging to the ubiquitin-proteasome system can be found in all clusters and PLK1 expression is higher in cluster 2 tumours compared to the others. However, many cell lines have been reported throughout literature to be insensitive to these drugs 51 56 . Moreover, we observed a significant synergic action of Bortezomib and PLK1 inhibitors at several dosages on both cell lines, not found when BI6727 was considered in combination with the other two signature-related drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Three highly homologous AKT isoforms (i.e., AKT1, AKT2, and AKT3) may play different roles. Increased AKT3 expression not only promoted prostate cancer proliferation [ 55 ], but also conferred resistance to AKT inhibitor in breast cancer [ 56 ] and PLK inhibitors in human colorectal cancer [ 57 ]. Inhibiting AKT3 and PI3KCA enhanced chemotherapy sensitivity in glioblastoma multiforme cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of PLK1 has been shown to cause cell cycle arrest at the G2/M phase and to increase apoptosis in cancer cells [ 9 , 11 , 12 ]. Recently, Nonomiya et al reported that the upregulation of p-glycoprotein and AKT3 and the downregulation of Myc contributed to the resistance of several PLK inhibitors [ 10 ]. The resistance mechanisms of PLK inhibitors are a critical issue to improve the clinical benefits of said PLK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Volasertib (BI 6727) is a PLK1 inhibitor [ 9 ] and has been reported as a potential therapeutic agent in multiple cancer types. Recently, PLK1 inhibitor-resistant cell lines have been reported [ 10 ]. To improve the clinical benefits of PLK inhibitors, combinations of anticancer therapies with high efficacy and low toxicities are highly sought after.…”
Section: Introductionmentioning
confidence: 99%